Acute effects of methylphenidate on energy balance in healthy men and women - Lorello, Claudio (University of Ottawa (Canada), 2007)
This thesis attempts to clarify the impact of methylphenidate hydrochloride (MPH) on key components involved in energy balance, specifically, resting energy (REE) and postprandial energy expenditure (PEE), substrate oxidation, energy intake and appetite. A double-blind, randomized, placebo-controlled, cross-over study was conducted to measure any differences between MPH and placebo treatments. MPH and/or placebo were administered orally (0.5 mg/kg) to seven healthy males (age: 19-37y, BMI: 19.8-30.5 kg/m2, body fat: 8-1-23.6%) and seven healthy females (age: 20-26y, BMI: 20.6-32.4 kg/m2, body fat: 18.8-42.1%). Indirect calorimetry was used to calculate energy expenditure variables while energy intake variables were measured during an ad libitum buffet-type lunch. Body composition was measured with dual energy x-ray absorptiometry (DEXA). The post-prandial energy expenditure (PEE) phase was measured over a 3-hour period. Vital signs (BP and HR) were assessed pre- and post-administration of MPH or placebo in every session. Results demonstrate that resting energy expenditure (REE) during MPH treatment increased over values obtained during the placebo session (1727.4 kcal/24h vs. 1612.3 kcal/24h, p<0.001). No changes in fasting respiratory exchange ratio (RER) were noted; however, significant decreases in post-prandial RER were found during the 30- to 90-min time interval (p<0.01). Although PEE continually decreased with time as expected, MPH treatment resulted in significantly greater PEE values at 90-min (MPH: 1946.9 kcal/24h +/- 290.0 vs. placebo: 1856.5 kcal/24h +/- 260.3, p<0.005). No statistical differences in side effects were noted between MPH and placebo treatment. Methylphenidate hydrochloride seemed to have a significant affect on energy expenditure and energy intake variables resulting in a potential net caloric deficit without significant changes in vital signs commonly associated with psychostimulant use. Keywords: Methylphenidate hydrochloride, energy balance, thermic effect of food, dual energy x-ray absorptiometry
Keywords: Biology, Physiology.